Cross-sectional and longitudinal trajectory analyses of sleep duration and frailty among middle-aged and older Chinese adults - Wei Zheng; Yan Sun; Xianling Liu; Miao Lu; Di Xu (Scientific Reports)
Abstract The relationship between sleep duration and frailty remains unclear, particularly regarding their bidirectional nature and temporal dynamics in the Chinese population. This study aimed to investigate the cross-sectional association, developmental trajectories, and interactions between sleep duration and frailty in Chinese middle-aged and older adults. Data were obtained from the China Health and Retirement Longitudinal Study (CHARLS), which included 12,942 participants for cross-sectional analysis and 11,192 participants for the longitudinal trajectory study. Latent growth models and cross-lagged panel models were utilized to explore the temporal effects of sleep duration on frailty and vice versa. Participants’ mean age was 59.29 ± 9.48 years, comprising 47.73% men and 52.27% women. Cross-sectional analysis revealed that, compared with participants with normal sleep duration (6–8 h), both Q1 (≤ 5 h, OR = 1.99, 95% CI 1.64–2.41, P < 0.001) and Q4 (> 8 h, OR = 1.50, 95% CI 1.12–2.02, P = 0.01) showed increased risks of frailty. The parallel latent growth model demonstrated that the initial level of sleep duration significantly negatively predicted the initial level of frailty (β = − 0.34, P < 0.001), while the rate of change in sleep duration negatively predicted the rate of change in frailty (β = − 0.61, P < 0.001). Conversely, the initial level of frailty significantly negatively predicted the initial level of sleep duration (β = − 0.36, P < 0.001), and the rate of change in frailty negatively predicted the rate of change in sleep duration (β = − 0.71, P < 0.001). Cross-lagged analysis indicated a bidirectional causal association between sleep duration and frailty, with the negative predictive effect of frailty on sleep duration being relatively stable, while sleep duration had a short-term effect on frailty. Our study revealed a U-shaped correlation between sleep duration and frailty risk in cross-sectional analysis and established a bidirectional relationship through longitudinal investigation. These findings underscore the importance of balanced sleep patterns and early screening for both conditions in middle-aged and older adults.